2008
DOI: 10.1177/0192623308327118
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocarcinogenic Susceptibility of Fenofibrate and Its Possible Mechanism of Carcinogenicity in a Two-Stage Hepatocarcinogenesis Model of rasH2 Mice

Abstract: Fenofibrate (FF) has previously been shown to induce hepatocellular neoplasia in a conventional mouse bioassay (NDA 1993), but there has been no report to examine the carcinogenic susceptibility of rasH2 mice to this chemical. In the present study, male rasH2 mice were subjected to a twothirds partial hepatectomy (PH), followed by an N-diethylnitrosamine (DEN) initiation twenty-four hours after PH, and given a diet containing 0, 1200, or 2400 ppm FF for seven weeks. The incidences of preneoplastic foci were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(45 reference statements)
1
11
0
Order By: Relevance
“…In our previous study, we performed a two-stage liver carcinogenesis experiment in transgenic mice carrying human prototype of c-Ha-ras gene (rasH2 mice) administered fenofibrate for 8 weeks after DEN initiation and reported that the numbers of CK8/18-positive foci were significantly increased in the livers of rasH2 mice [18]. In the present study, more hepatocellular foci were demonstrated in paraffin-embedded sections by CK8/18 immunohistochemistry than HE staining, and the total multiplicity of hepatocellular foci in HE-stained sections and positive for CK8/18 was 10.17 and 18.50, respectively, in Experiment I and 4.47 and 23.17, respectively, in Experiment II, although there were some foci being negative for CK8/18 in 5 of 6 mice in Experiment II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we performed a two-stage liver carcinogenesis experiment in transgenic mice carrying human prototype of c-Ha-ras gene (rasH2 mice) administered fenofibrate for 8 weeks after DEN initiation and reported that the numbers of CK8/18-positive foci were significantly increased in the livers of rasH2 mice [18]. In the present study, more hepatocellular foci were demonstrated in paraffin-embedded sections by CK8/18 immunohistochemistry than HE staining, and the total multiplicity of hepatocellular foci in HE-stained sections and positive for CK8/18 was 10.17 and 18.50, respectively, in Experiment I and 4.47 and 23.17, respectively, in Experiment II, although there were some foci being negative for CK8/18 in 5 of 6 mice in Experiment II.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cytokeratin (CK) 8/18 overexpression may drive neoplastic transformation of preneoplastic cells in GST-P-positive foci during rat hepatocarcinogenesis [16]. Moreover, we previously reported that hepatocellular altered foci induced in rasH2 mice given fenofibrate for 8 weeks after N-diethylnitrosamine (DEN) initiation were immunohistochemically stained with CK8/18 [18].Piperonyl butoxide (PBO) is a pesticide synergist that is widely used with pyrethroids for grain protection and as a domestic insecticide. PBO is a hepatocarcinogen in F344 rats fed a diet containing 1.2% PBO for 2 years [29] and CD-1 mice fed a diet containing 300 mg/kg/day PBO for 79 weeks [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…indicated that the expressions of genes related to blood vessel formation and MAPK cascade activation were significantly upregulated in splenic hemangiosarcomas in rasH2 Tg mice treated with troglitazone and UR. Kawai et al (2008) showed enhanced mRNA expressions of the ras/MAPK pathway and cell cycle genes in the livers of the rasH2 Tg mice treated with FF for 7 weeks after DEN initiation. Most of the toxicogenomic studies in the rasH2 Tg mice were conducted with tissues showing obvious cancerous changes as described above.…”
Section: Introductionmentioning
confidence: 96%
“…They also demonstrated that 5 injections of urethane (UR) at 2-day intervals induced the formation of lung tumors at 5 weeks after the UR treatment (Okamura et al, 2006). In twostage carcinogenesis models established using rasH2 Tg mice, 16 weeks of troglitazone administration after UR initiation induced the formation of splenic hemangiosarcomas and 7 weeks of fenofibrate (FF) administration after N-diethylnitrosamine (DEN) initiation induced hepatocarcinogenesis (Kawai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%